2019
DOI: 10.3389/fneur.2019.00299
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Heparinization During Mechanical Thrombectomy in Acute Ischemic Stroke

Abstract: Background: The benefits of heparization during mechanical thrombectomy (MT) with newer generation thrombectomy devices, and if it is counterbalanced by the increased risk of intracranial hemorrhage (ICH) remain unknown. Methods: We included eligible patients who underwent MT from the ANGEL registry study (2015-2017) in China. Subjects in the current analysis were dichotomized into two groups according to whether adequate heparinization during MT was performed. In the heparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…20,21 Observational studies found that unfractionated heparin might improve functional outcomes in patients with ischaemic stroke treated with endovascular treatment. 3,5,11 In our trial, we did find higher recanalisation rates in the unfractionated heparin group. However, this benefit did not outweigh the increased risk of symptomatic intracranial haemorrhage.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…20,21 Observational studies found that unfractionated heparin might improve functional outcomes in patients with ischaemic stroke treated with endovascular treatment. 3,5,11 In our trial, we did find higher recanalisation rates in the unfractionated heparin group. However, this benefit did not outweigh the increased risk of symptomatic intracranial haemorrhage.…”
Section: Discussionmentioning
confidence: 41%
“…3,4 However, for aspirin and heparin, the potential benefits are not known on whether its periprocedural use outweigh the potentially increased risk of symptomatic intracranial haemorrhage. 3,5 Guidelines advise against the early administration of aspirin after treatment with intravenous thrombolytics because of its increased risk of sympto matic intracranial haemorrhage without evidence for a beneficial effect in a previous trial. 6,7 However, this trial was done in patients with ischaemic stroke treated with intravenous thrombolytics before the introduction of endovascular treatment, and the 4•3% risk of symptomatic intracranial haemorrhage in the intervention group was low.…”
Section: Introductionmentioning
confidence: 99%
“…All our participants were enrolled from the Acute Ischemic Stroke Cooperation Group of Endovascular Treatment (ANGEL) study, a multicentre prospective registry study aiming to evaluate MT delivery and to improve the MT algorithm in clinical practice from June 2015 to December 2017 in China. Details about the design of the ANGEL study have been reported [10,11]. (The design, inclusion/exclusion criteria, data collection and endovascular treatment of the study are described in the Supporting information.)…”
Section: Study Design and Patient Enrolmentmentioning
confidence: 99%
“…The TREVO 2-tial (Winningham et al, 2018 ) and multi-MERCI trial (Nahab et al, 2012 ) found neutral effects of periprocedural heparin on sICH and mortality, but a positive effect on functional outcome. The ANGEL- collaborators from China (Yang et al, 2019 ) however showed a higher rate of sICH and distal embolization with increasing total heparin dose (the latter could be due to a higher frequency of intracranial atherosclerosis). Regarding the sole impact of heparin in flush fluids during EVT, there are hardly any data available.…”
Section: Discussionmentioning
confidence: 99%